Mapeamento convencional e digital de solos na folha topográfica de Marechal Cândido Rondon - PR - BR - Silva, Bruno Aparecido da (2017)
The pedometrics techniques have been used to obtain detailed information about soils. For example, the elaboration of Digital Soil Maps (MDS) instead to the Conventional Soil Mapping (MCS). The reliability of the MDS is one of the reasons for the popularization of this technique in the academic researches. The goal was to elaborate the Conventional Soil Map and the Digital Soil Map considering the Topographic Chart of Marechal Cândido Rondon (SG-21-X-B- VI-2), western region of the State of Paraná, Brazil. Satellite images interpretation and fieldworks to describe and classify the soils up to the 2nd categorical level were used to map the soils units in the MCS. The MDS procedures consisted in the morphometric data from the SRTM (Shuttle Topography Mission - 30 meters spatial resolution), using the Geographic Information Systems (GIS) Qgis 2.10, Saga 2.2.6 and Arcgis 10.4. The morphometric data consist in altimetry, slope, sediment transport capacity index and topographic humidity index. The Topodata Project (Brazilian Geomorphometric Database) provide the terrain curvature data. In ArcGis 10.4 the topographical attributes processed consider their respective weights, according to the intensity of the pedogenetics processes, resulting in four mapping units. The evaluation of the soils maps consisted of the observation of 160 points in fieldwork. LV, NV, RR + RL + CX and GX + RY. represent the four units mapped. Validation from the fieldwork indicate 76.3% of correspondence to MCS and 71.9% to MDS. The relationship between the MDS and the MCS indicate 66% of similarity. The most satisfactory results of ‘producer’s and ‘user’s errors refers to RR+RL+CX and GX+RY, respectively. The lowest ‘producer’s and ‘user’s errors were to GX+RY and NV, respectively. The MCS and MDS allow to obtain more detailed information about soils distribution in the landscape, nearly to the scale of 1:50 000. Topographic attributes were important sources of information to observe distinct sectors of the landscape that may be associated with pedogenetic processes. MDS techniques should be complemented with morphometric index, and others data, preferably on a detail scale for better results.